Industrial Cores and Peripheries in Brazil - Ricardo Ruiz; Edson Domingues (European Regional Science Association (ERSA), 2005)
There is considerable evidence to demonstrate that the industrial localization in developing countries shows high level of spatial concentration, and the industrial decentralization is quite restricted to few isolated regions. The aim of this paper is to analyze the Brazilian case to identify the industrial cores and to find out whether Brazil follows this conventional view on industrial location in developing countries. This study is based on a database that merges two sets of data: the first describes 35000 industrial firms, and the second has information on the economic, social and urban structure of 5500 cities (year 2000). Based on these datasets, the industrial cores and their respective peripheries are identified, classified, and discussed. The main preliminary conclusions are: (1) Brazil has several industrial cores with different scales, structures, and regional level of integration; (2) there are regions with growing industrial peripheries that are strongly tied to the primary cores; these are what we called "industrial axes”; (3) however, we also identified regions that did not manage to build peripheries able to assimilate spillovers generated by its industrial centers; these are the "industrial islands”. Our main conclusion is: the Brazilian economic space is a mixed case. It is not a set of disconnected or isolated industrial islands, but it is still behind a full regional economic integration.
Keywords: 330